Plasma metabolic signatures reveal the regulatory effect of exercise training in db/db mice1. Issue 9 (11th September 2015) - Xiang, L.; Cheang, W. S.; Lin, S. H.; Wang, L.; Li, Y. L.; Huang, Y.; Cai, Z. W.
<x xml:space="preserve">Abstract</x> Regulatory effect of moderate exercise training on fatty acid oxidation.